АPPOSITIVE STRUCTURES AS SYNONYMIC DISCOURSE INNOVATIONS IN FRENCH FICTION OF THE 20th – EARLY 21st CENTURIES - Anastasiia V. Lepetiukha (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2022)
In this article the appositive structures of modern French fiction are studied in the continuum language → discourse and defined as two-basis (with several transformational terminal chains) synonymic transforms of the virtual (linguistic) primary subordinate proposition which are formed in the space of the operating time of a thought movement and actualized in the form of compressed discourse innovations with the implicit predication. The goal of this research is the establishment of the structural-semantic typology of mono- and polypredicative utterances with the appositive synonymic transforms of French fiction of the XXth – the beginning of the XXIst centuries, the inverse reconstruction (discourse → language) of the virtual transformational processes and of the primary proposition within the functional‑semantic macrofield of the analyzed appositive constructions and the justification of the co(n)textual pertinence of the actualized appositive preferential options. In the article the method of the inverse reconstruction of the systemic (linguistic) transformational operations is used with the aim to reveal all the members of synonymic chains. The “alternative” linguistic experiment, that consists on the artificial substitution by the recipient of some utterance of the analyzed discursive fragment with the synonymic utterance, allows to determine the degree of the co(n)textual pertinence of the primary proposition and of each synonymic transform. The immediately and distantly pre-, inter- and postpositive mono- and polysynonymic (with the polysynonymy in the level of a syntagm and the utterance) appositive preferential options with explicative, concessive, conditional and causal semantic values are distinguished. They revealed the mono- and polypredicative utterances: a) with explicit actant-referent point of the appositive segment; b) with implicit actant and indirect designation of the appositive referent by the immediate actant markers in the form of possessive, demonstrative et al. adjectives that introduce the substantive which marks the part of body, the human condition, the feeling etc.; c) with implicit actant and indirect designation of the appositive referent by the distant actant markers (most often by the personal pronouns direct and indirect complements). The virtual transformational processes are inversely reconstructed and the degree of the co(n)textual pertinence of each member of the synonymic chain of analyzed appositive constructions conditioned by the author’s intention to avoid the reactualization of the exteriorized referents, the overload of the co(n)text with complex predicative constructions or by his idiostylistic peculiarities, is determined.